2017
DOI: 10.1016/j.ajhg.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Unified Sequence-Based Association Tests Allowing for Multiple Functional Annotations and Meta-analysis of Noncoding Variation in Metabochip Data

Abstract: Substantial progress has been made in the functional annotation of genetic variation in the human genome. Integrative analysis that incorporates such functional annotations into sequencing studies can aid the discovery of disease-associated genetic variants, especially those with unknown function and located outside protein-coding regions. Direct incorporation of one functional annotation as weight in existing dispersion and burden tests can suffer substantial loss of power when the functional annotation is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…In this paper, we have proposed a unified framework for meta-analysis of RVs, called the aSPU-meta test. Although we did not focus on the use of variantspecific or study-specific weights, appropriate incorporation of such weights may increase the statistical power and interpretation, for example, using the functional weights (He, Xu, Lee, & Ionita-Laza, 2017;Ma & Wei, 2019;Zhan & Liu, 2015). In addition, we showed that our aSPUmeta test was more powerful than many existing tests, being either the most powerful or close to the most powerful ones, across various simulation set-ups, and in particular, was able to identify novel genes in our real data analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we have proposed a unified framework for meta-analysis of RVs, called the aSPU-meta test. Although we did not focus on the use of variantspecific or study-specific weights, appropriate incorporation of such weights may increase the statistical power and interpretation, for example, using the functional weights (He, Xu, Lee, & Ionita-Laza, 2017;Ma & Wei, 2019;Zhan & Liu, 2015). In addition, we showed that our aSPUmeta test was more powerful than many existing tests, being either the most powerful or close to the most powerful ones, across various simulation set-ups, and in particular, was able to identify novel genes in our real data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our data example, gene B4GALNT2 was discovered by the aSPU-meta test for the AA subjects in the presence of high between-study heterogeneity and a large number of likely neutral RVs; in contrast, it was missed by competing methods. Although we did not focus on the use of variantspecific or study-specific weights, appropriate incorporation of such weights may increase the statistical power and interpretation, for example, using the functional weights (He, Xu, Lee, & Ionita-Laza, 2017;Ma & Wei, 2019;Zhan & Liu, 2015). We also note that, similar to other competing tests for RVs, one potential drawback of the current implementation of the aSPU-meta test using Monte-Carlo simulations is its use of the asymptotic normal distribution of the score vector, which may not hold for extremely unbalanced case-control studies, and other resampling methods like permutation-based ones may need to be adopted for more accurate p value calculations (Dey et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, if the selected values do not reflect the true model, then the corresponding test might be underpowered (Selyeong Lee et al, ; Ray et al, ). To overcome such issues, minimum p value‐based omnibus tests have been proposed, which aggregate results across different values of the parameters to produce robust results (Dutta et al, ; Engel et al, ; He, Xu, Lee, & Ionita‐Laza, ; Urrutia et al, ; Zhan et al, ). Here, we use the same strategy to formulate robust tests across different choices of ΣS, ΣP, and ΣG.…”
Section: Methodsmentioning
confidence: 99%
“…Although the linear (weighted) kernels are still most widely applied in genetic association studies, owing to its biological interpretability and computational efficiency, there have been recent attempts to design kernels that adapt to more complex signal structures by taking into account prior biological knowledge. For example, new variance component kernels have been proposed to accommodate functional annotations of noncoding variations in the mixed-effects model framework (Hao, Zeng, Zhang, & Zhou, 2018;Z. He, Xu, Lee, & Ionita-Laza, 2017).…”
Section: Variance Component Kernelsmentioning
confidence: 99%